(3JMdjd GdEbJUGO Gdcdjs - (3eYQha(B, (3ghTjGQgs ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2005)
(3eaghe Yde GdEbJUGO hCQcGfg GdCSGSjI ,CSGSjGJ GdEbJUGO Gdcdj ,GdfGJL GdeMdj GdELeGdj GdeVGYa hGdeYLd ,GdJbfjGJ GdOhQjI ,GdJMdjd Gdcej hGdJUMjM GdacQj JLGg GdJbdHGJ GdOhQjI hGdJhGRf GdEbJUGOj ,GdJVNe hGdeHGWdI ,GdfbhO hGdHfhc hGdSjGSI GdfbOjI ,GdSGSI GdeGdjI ,CShGb GdUQa GdCLfHj hejRGf GdeOahYGJ Gdfeh hGdJfejIs
(3GdeQGLY U(B.401s
Keywords: (3GdGbJUGO Gdcdjs